Relevance of chromosome 13 aberrations in canine tumours - Reimann-Berg, N.; Escobar, H. Murua; Nolte, I. (Tierärztliche Praxis Ausgabe K: Kleintiere / Heimtiere, 2012)
For human tumours there are many reports documenting the correlation between chromosome aberrations and tumour entities. Due to the complex canine karyotypic pattern (78 chromosomes), cytogenetic studies of tumours of the dog are rare. However, the reports in the literature show, that canine chromosome 13 (CFA 13) is predominantly involved in chromosomal changes. Interestingly, CFA 13 shows high homology to regions on the human chromosomes 4 (HSA 4) and 8 (HSA 8), which harbour the proto-oncogenes c-KIT and c-MYC. Both of these genes are involved in the development and progression of some human and canine tumour diseases.
Keywords: Tumour cytogenetic analyses; canine chromosome 13; c-MYC; c-KIT; comparative oncology